Origine de l’assurance et tableau chronologique - Moreau, Rémi (Assurances, 1991)
The author provides a short history of insurance from its origins to the beginning of the nineteenth century. Insurance, in its actual form, is not one of the oldest commercial institutions known to man. Its beginnings were complex and could be traced to mutual forms of protection by cities and leagues during the Middle Ages. This article gives a chronological table of some of the most important dates on the beginnings of insurance and its evolution from the fourteenth to nineteenth centuries.